Assessing the Compliance of Online Marketplace Mechanism with Shari’ah Law (Case Study of Bukalapak) - Iryandi Masputra; Nashr Akbar (AL- IKTISAB Journal of Islamic Economic Law, 2017)
Bukalapak is one of the biggest online marketplace in Indonesia. Bukalapak providesa place for trading for sellers and buyers, utilizing the applications on the internet as aspace to trade. The objective of the study is to assess the the compliance of product, buyerand seller verification system, payment and delivery transaction system of Bukalapakwith the Shariah law. This research uses a qualitative approach; interview and observation.The collected data will be analysed with interactive analysis model by Miles andHuberman. The result of this study shows that as an online marketplace, Bukalapakcomplies with the legal standards of Shariah law which is based on ijab qabul between theseller and the buyer, also there is a form of liability or indemnity imposed by Bukalapakwith the view of balance and fairness between all Bukalapak users. The result also showsthat Bukalapak had been running based on honesty and openness so that it is able todevelop the market based on Islamic economics. Hence, it earns the trust from the sellersand the buyers as a place for buying and selling.